INTEGRATING GENDER EQUALITY INTO CURRICULUM DEVELOPMENT: A CASE STUDY IN ISLAMIC EDUCATION AT THE ELEMENTARY LEVEL - Muqarramah Sulaiman Kurdi (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2024)
This study explores the integration of gender equality into curriculum development within the context of Islamic education at the elementary level. Employing a qualitative case study approach, data were collected through interviews, document analysis, and classroom observations at an Islamic elementary school known for its progressive curriculum initiatives. The findings reveal that while there is a growing awareness among educators regarding the importance of gender equality, its implementation in teaching materials and classroom practices remains limited and often reinforces traditional gender roles. Curriculum documents tend to portray male figures more dominantly, while female figures are underrepresented or confined to domestic roles. However, some educators have begun introducing alternative narratives and expressed openness to professional development on gender-sensitive pedagogy. This study concludes that integrating gender equality into Islamic education requires collaborative curriculum reform, culturally contextualized training, and alignment with core Islamic values. The results contribute to broader efforts in promoting inclusive education and offer practical insights for policymakers, educators, and curriculum developers.